ANALISIS SINERGITAS AKTOR GOOD GOVERNANCE DALAM PENGELOLAAN SAMPAH KOTA PEKANBARU - M Fajar Anugerah; Muhammad Fadhli; Mhd Rafi Yahya (LPPM Universitas Abdurrab, 2024)
Among the environmental issues that are of concern in sustainable development is waste management. This can be done through synergy in the form of good coordination between the government, the private sector and the community so that later it will generate public awareness in the process of reducing, recycling and using environmentally friendly waste processing technologies. The phenomenon of decreasing public awareness in Pekanbaru City regarding waste management that has an impact on health and reducing environmental impacts is an urgency in this research. So this study aims to analyze the synergy of good governance actors in waste management efforts in Pekanbaru City. This study used a qualitative method involving the people of Pekanbaru City as informants in this study. Collecting data in this study using a purposive sampling technique. The use of this technique can help researchers to determine the suitability of informants with the theme of this research. The results of this study are that the synergy between good governance actors has been going well by carrying out their respective functions, especially in waste management. Consistency and awareness of each actor is expected so that there is synergy in cleaning management, especially in waste management in order to create a civilized city of Pekanbaru.